The Repulsive Casimir Force with Metallic Ellipsoid Structure - Yujuan Hu; Ruo Sun; Zhixiang Huang; Xianliang Wu (Journal of Nanotechnology)
We propose a new structure, one plate with a hole above the ellipsoid and the other plate with a hole below the ellipsoid, to obtain a repulsive Casimir force. The force was obtained numerically by using the in-house FDTD method, based on Maxwell’s stress tensor and harmonic expansion. The code can be verified by calculating the force of a perfect-metal ellipsoid centered above a perfect-metal plate with a hole. Our numerical method can effectively simulate the Casimir force by reducing the total simulated time. The further numerical results of realistic dielectric material immersing in fluids or adding other plates above the ellipsoid are also presented. It is not surprising to find that the larger differences can be achieved by varying the parameters such as the center-center separation, medium immersed, and the dielectric material of the structure. Thus, it is possible to tune these parameters relatively in the realistic microelectromechanical systems to overcome stiction and friction problems.